Synthesis and catalytic activity of Cu-Cr-O-TiO2 composites for the thermal decomposition of ammonium per-chlorate: enhanced decomposition rate of fuel for solid rocket motors - Kumar H.; Tengli P.N.; Mishra V.K.; Tripathi P.; Pal D.B.; Mishra P.K. (My University, 2025)
This study presents the sol-gel synthesis of Cu-Cr-O·nTiO2 particles calcined at different temperatures and their catalytic effects on thermal decompostion of AP. The study focuses on the impact of crystallite size, shape and concentration of TiO2 in the catalyst composition on the thermal decomposition behaviour of ammonium per-chlorate (AP). During synthesis, the molar ratio of Cu/Cr was kept to 0.7 and TiO2 nanoparticles were added into Cu-Cr-O-citric acid solution at different molar ratios to form three different compositions of the catalyst Cu-Cr-O·nTiO2 (n = 0.5, 0.7 and 0.9 mol%). The effect of temperature on the thermal, structural and spectroscopic properties of the different Cu-Cr-O compositions was also studied by calcining them at two different temperatures, 300 and 1050 °C. Post synthesis characterizations of the prepared catalysts were carried out by using XRD, FT-IR, SEM, EDAX and TEM (with SAED pattern) techniques. The desired qualification of Cu-Cr-O-citric acid (the precursor of the catalyst) and the final compositions of the catalysts were carried out by using thermogravimetric and differential thermal analysis (TG-DTA) techniques. The efficiency of the synthesized catalysts was evaluated on thermal decomposition behaviour of AP using TG-DTA techniques. The Cu-Cr-O·nTiO2 composition with the molar ratio of n = 0.7 was found to be the most efficient catalyst for decomposition of AP; it was much better than other laboratory prepared samples (n = 0.5 and 0.9) as well as the industrial catalyst (i.e. activated copper chromite (ACR); Cu-Cr-O). Further experimental work showed that addition of 10 wt% Cu-Cr-O·0.7TiO2 into AP significantly lowered the AP decomposition temperature to 306 °C from 385 °C and was accompanied by a very sharp exothermic peak indicating a single stage decomposition. The excellent finding of the study was also verified by heat of reaction (i.e. calibrated delta H) values. This study finds potential application due to the remarkable enhancement in the thermal decomposition rate of the AP used as oxidizer in propellant of solid rocket motors (SRMs) and space vehicles (SVs) at lower decomposition temperature. The fast decomposition rate of oxidizer at lower decomposition temperature enhances the efficiency of fuel which ultimately will enhance the efficiency of SRMs and SVs. © The Royal Society of Chemistry.